The Role Of Bank Syariah Indonesia In Enhancing Cash Waqf Literacy Among The Malay Community Of Bengkalis - Nur Azlina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study investigates the strategic role of Bank Syariah Indonesia (BSI) KCP Bengkalis in enhancing cash waqf literacy within the culturally dense Malay community of Bengkalis Regency. Using a qualitative approach with a descriptive field research design, data were gathered through semi-structured interviews with key stakeholders comprising BSI management, the Ministry of Religious Affairs (Kemenag), BAZNAS, and the Indonesian Waqf Board (BWI) supplemented by questionnaires distributed to local waqf managers (nazhir), and analyzed using the Miles and Huberman interactive model. The findings reveal that BSI KCP Bengkalis exerts a tangible empirical impact through three interconnected dimensions: active financial education by implementing a culturally-adaptive financial literacy model that integrates digital socialization with traditional community gatherings; institutional networking with BWI and BAZNAS to transition public trust toward accountable, institutional nazhir management; and digital-based cash waqf services through the optimization of the e-waqf feature on mobile banking. These integrated strategies successfully mitigate deeply rooted local barriers, specifically the persistent cognitive bias of viewing waqf solely as immovable physical assets, and the community's jurisprudential skepticism regarding digital fiqh and cyber security. Analyzed through Financial Intermediation and Social Capital theories, this study concludes that digital financial inclusion in rural areas cannot rely on top-down infrastructure approaches alone, but must be symmetrically aligned with local socio-cultural capital to achieve digital accountability